Development of deflector flat spray nozzle with mixed of water and organic citric acid for emissions trap and cooling in the kitchen hood ventilation system - Sies, Mohamad Farid (2018)
The growth of food industry is rapidly-evolving due to the increase of human population, which results in changes to the cooking technology development. This condition leads to increased pollution rate, especially air and water pollution. Recently, several technologies and research are developed to improve the commercial kitchen industry, especially in hotels and restaurants. The function of kitchen hood is to remove gas, odour, heat and steam during cooking process. The main purpose of this study is to introduce mist spray (atomization) to replace the water spray system in the existing kitchen hood. In addition, this study compared the existing (conventional) nozzles in the market such as KSJB model (water spray) and AL75 model (mist spray). Then, this study compared two nozzle designs of deflector nozzles that is ND2.5 A1.0 and ND2.5 B1.0. The difference between these two nozzles is the swirl angle. The swirl angles for ND2.5 A1.0 and ND2.5 B1.0 are 10o and 15o respectively. The use of the new nozzles is to reduce water consumption in the kitchen hood ventilation system. The other function is to introduce organic citric acid as an agent to absorb gas emitted during cooking, besides looking at the effect of nozzle design in limiting gas emission and reducing kitchen hood temperature during cooking. Several methods were used in this study, such as the development of a small size kitchen hood with one nozzle using water sensitive paper (WSP) to spray droplets with fluid pressure from one to six bar, using a gas analyzer for gas reading and thermocouple for temperature reading in the kitchen hood system. The results obtained from the comparison between KSJB model and AL75 model showed that the mist spray nozzle (AL75) is better than the water spray (KSJB) model. On average, the difference in gas emission percentage between AL75 and KSJB is 15.08 – 35.82 % while the difference in temperature is 2.98 – 11.35 %. Then, the comparison between the new nozzles shows that ND2.5 A1.0 is better than ND 2.5B1.0. On average, the difference in gas emission percentage between ND2.5 A1.0 and ND 2.5B1.0 is 2.65 – 24.32 % while the difference in temperature is 6.48 – 14.86 %. Lastly, comparison between AL75 and the new model which is ND2.5 A1.0 shows that ND2.5 A1.0 has better performance than AL75. On average, the difference in gas emission percentage between these two models is 13.12 – 33 % while the difference in temperature is 11.84 – 20.22 %. However, the AL75 nozzle can reduce water consumption by 60 – 80 % as compared to KSJB, depending on air pressure. The results show that the atomization nozzles (AL75, ND2.5 A1.0 and ND2.5 B1.0) have better effect than the water spray (KSJB) nozzle. The factors that improves kitchen hood performance are high spray angle, large droplet size and the usage of organic citric acid. In addition, mist spray can reduce water consumption and water pollution. In fact, the use of organic citric acid can reduce air pollution in the cooking process. For future studies, it is suggested to use an actual kitchen hood size for testing and the quantity for each nozzle type is increased in the kitchen hood system.